Urban Renewal Planning Criteria for Small Historic Towns in Croatia (Prostor, 2024)
Small historical towns are an important factor in the spatial identity and urban tradition of Croatia. Their list was determined using a multi-criteria model and identity features were evaluated. Criteria for urban renewal planning were proposed depending on the evaluation. These are: preservation and maintenance; improvement and advancement of identity features; and introduction of new structures and content into neglected parts of the city.